Wolf Conservation and Management in Spain, An Open Debate - Ordiz, Andrés; Canestrari, Daniela; Echegaray, Jorge (Frontiers in Environmental Science, 2022)
Wolf management in Spain is remarkably different at regional scales. South of Douro river, wolves are protected, north of Douro wolves can be hunted, and culling occurs on both sides. After a formal request to include wolves in the Spanish Red List of Threatened Species, wolves have been “listed”, but not as a vulnerable species. Recreational hunting will no longer be a wolf management option, while culling is still allowed. We describe the process to raise wolf protection at the state level, and the factors that should be relevant to guide apex-predator management. Restricting lethal control and favoring predator-prey interactions by reducing livestock depredation should be more feasible with an overarching policy that is binding over the whole range of the species in Spain.